Zeta potential and doping in polyaniline dispersions - de Medeiros, DWO; Santos, D. S.; Dantas, TNC; Pereira, M. R.; Giacometti, A.; Fonseca, JLC (Oficyna Wydawnicza Politechniki Wroclawskiej, 2003)
Polyaniline (PAni) has been classified as an intractable polymer, particularly in its conducting form, the emeraldine salt (ES). Therefore one can consider the mixture of water and PAni as a suspension. The conducting form of PAni can be obtained by a doping process known as acid doping, in which a strong acid turns PAni from its insulating form, the emeraldine base (EB), into the conducting form, the emeraldine salt. With the objective of establishing a correlation between the doping level and the zeta potential of polyaniline dispersions, polyaniline + HCl aqueous suspensions were prepared. Positive zeta potential values for the various suspensions of PAni showed that it acquired positive charges after the doping process. It was also observed an increase in zeta potential values as HCl concentration increased, which could be correlated to UV-visible spectra of PAni suspensions.
Keywords: polyaniline; electrophoretic mobility; zeta potential; doping